2016
DOI: 10.21859/mej-1035141
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations in domestic violence related researches

Abstract: Background and Aim: Violence against women is one of the serious causes of disability and death of women with a high prevalence rate. Violence against women ethically is a sensitive research topic because it may engender physical, psychological, social and financial costs to those involved in research, to both researchers and participants. This study conducted with the aim of determining the ethical considerations in domestic violence research.Methods: In this review article, study of books and purposeful sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Undoubtedly, extensive education for various groups of the society including the service providers about IPV, its physical and mental consequences, dissenting opinions for seeking help, gender equality, existing services for the victims and the manner of accessing them has an important role in advocacy for abused women and strengthening their unofficial and official support system because educating and discussing the subject of violence at the society level would change it from a personal matter into a publicly known and more understandable subject. it would also help the voices of abused women to be heard (Taherkhani, 2016). This way, the traditional beliefs and attitudes related to patriarchy ideology might also be modified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, extensive education for various groups of the society including the service providers about IPV, its physical and mental consequences, dissenting opinions for seeking help, gender equality, existing services for the victims and the manner of accessing them has an important role in advocacy for abused women and strengthening their unofficial and official support system because educating and discussing the subject of violence at the society level would change it from a personal matter into a publicly known and more understandable subject. it would also help the voices of abused women to be heard (Taherkhani, 2016). This way, the traditional beliefs and attitudes related to patriarchy ideology might also be modified.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from all the participants. When designing and conducting the study, we observed the ethical guidelines recommended for the research on domestic violence against women (Department of Gender and Women’s Health Family and Community Health World Health Organization, 2001; Taherkhani, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The study was confirmed by the Ethics Committee of the Shahid Beheshti University of Medical Sciences (400/4834). When conducting and designing the study, the ethical guidelines recommended for the study on domestic violence against women were observed (Taherkhani, 2016; World Health Organization, Family and Community Health, Department of Gender and Women’s Health, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…According to the global research conducted under WHO monitoring, 1 out of 4 women is exposed to violence and almost 75% of women in the world have experienced at least violence for once [4]. The results of studies performed in Iran have also confirmed the extent of this social health problem [5]. According to a national survey in 18 provinces of Iran, domestic violence against women has been 66% [6].…”
Section: Introductionmentioning
confidence: 99%